TRADISI MALAM KHATAMAN PENGANTIN PEREMPUAN SUKU MELAYU TAMIANG: Analisis Tindakan Sosial Max Weber - Nur Arifa (Mukaddimah: Jurnal Studi Islam, 2022)
The tradition of khataman is that for the most part, the most popular extradition in islamic root societies in Indonesia, the Indonesian economy, and its Indonesia, are eroding off certain areas. this paper will discuss the traditional night in an earthquake monastery of Malay women and temperatures in wtlday as the theory used was the social teori Max Weber. It is a measured measure of objective and therefore gives support to others. Four social actions as unlucky as (1) deactivation of continue to be credited to me by the army of emastonat for fishing vessels, (2) traditional east tour team mndakan for the perpetrators of a tertenu tradition. As a result of the preservation of tradition, (3) the insmumental rationality, a result of people's conscious thinking on the basis of their capacity and ability to implement it, (4) rational mtlai being nitglath-mlai having succeeded. Based on the implementation of the agreement, it will be the result of the acquisition of the mont, mlat and the completion of the dart targeting khataman tradition. Keyword: khataman, hadis, sosial action